2013
DOI: 10.1016/j.devcel.2013.05.023
|View full text |Cite
|
Sign up to set email alerts
|

The Drosophila Nuclear Lamina Protein Otefin Is Required for Germline Stem Cell Survival

Abstract: Summary LEM domain (LEM-D) proteins are components of an extensive protein network that assembles beneath the inner nuclear envelope. Defects in LEM-D proteins cause tissue-restricted human diseases associated with altered stem cell homeostasis. Otefin (Ote) is a Drosophila LEM-D protein that is intrinsically required for female germline stem cells (GSCs) maintenance. Previous studies linked Ote loss with transcriptional activation of the key differentiation gene, bag-of-marbles (bam), leading to the model tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
65
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(70 citation statements)
references
References 54 publications
(67 reference statements)
4
65
1
Order By: Relevance
“…To determine whether Bocks contributes to nuclear lamina function in early stages of germ-cell development, we examined larval gonads. Previous studies have shown that loss of Ote reduces the number of primordial germ cells (PGCs) in the third-instar larval gonads (Barton et al 2013). To understand whether Bocks protects PGCs from Ote loss, we stained lem-d double-mutant larval gonads with antibodies against Vasa and Spectrin (Figure 7).…”
Section: Generation Of Bocks Mutantsmentioning
confidence: 99%
See 4 more Smart Citations
“…To determine whether Bocks contributes to nuclear lamina function in early stages of germ-cell development, we examined larval gonads. Previous studies have shown that loss of Ote reduces the number of primordial germ cells (PGCs) in the third-instar larval gonads (Barton et al 2013). To understand whether Bocks protects PGCs from Ote loss, we stained lem-d double-mutant larval gonads with antibodies against Vasa and Spectrin (Figure 7).…”
Section: Generation Of Bocks Mutantsmentioning
confidence: 99%
“…Crosses were carried out in vials at 25°, unless otherwise noted. Stocks used in this study include y 1 w 67c23 (the wild-type reference control), two dMAN1 alleles [dMAN1 D81 and dMAN1 D26 (Pinto et al 2008)], and two ote alleles [ote B279-G and ote halPk (Barton et al 2013)]. …”
Section: Drosophila Stocks and Culture Conditionsmentioning
confidence: 99%
See 3 more Smart Citations